Postoperative Complications and Long-Term Results after Primary Cardiac Sarcoma Resection - Kavakbasi, Erhan; Scheld, Hans Heinrich; Kessler, Torsten; Sindermann, Jürgen R.; Kösek, Volkan; Tjan, T. D. T.; Martens, Sven; Hoffmeier, Andreas (The Thoracic and Cardiovascular Surgeon, 2018)
Background Primary malignant cardiac tumors rarely occur in clinical care. Little is known about the impact of a parameter on postoperative survival.Methods From May 1991 to May 2014, a total of 24 patients underwent surgical treatment of a primary cardiac sarcoma in our center. We analyzed our clinical database retrospectively for information on patient characteristics and treatment data. The follow-up could be completed to 91.7%.Results Angiosarcoma and non-otherwise-specified sarcoma were the most common tumor entities. R0 resection was achieved in most cases. Postoperative mortality within the first 30 days was 20.8% (n = 5). In four of these five cases, postoperative low-output cardiac failure was the leading cause of death. The cumulative survival rate was 77.3% after 30 days, 68.2% after 3 months, 50.0% after 6 months, 45.0% after 12 months, and 18.0% after 24 months. The mean survival time in the whole group was 47.0 months. A low tumor differentiation was associated with low mean survival, but this was not statistically significant. Mean survival of sarcoma was higher after R0 resection. There was no significant rate of survival difference regarding the adjuvant therapy concept.Conclusion Extended surgery alone or in combination with chemo- and/or radiotherapy may be successful in certain cases and may offer a satisfactory quality of life. The establishment of a multicenter heart tumor register in Germany is necessary to increase the number of cases in studies, get more remarkable study results, and standardize the diagnosis and therapy.
Keywords: primary malignant cardiac tumors; cardiac tumor resection; cardiac sarcoma; postoperative course; survival; complications